THE IMPORTANCE OF TEACHING QUANTUM PHYSICS IN GENERAL SECONDARY SCHOOLS - Abdurazzokh Nizamiddinovich Ernazarov; Azizbek Farkhodovich Khudayberganov; Tajibayeva J.T. (European Science Publishing, 2024)
This article discusses the importance of teaching quantum physics in general secondary schools and the challenges in teaching the department.
Keywords: Quantum physics, mathematical apparatus, theoretical concept, De Broglie hypothesis.